Preparation method and preparation device of iron-based coating

Through the composite technology of laser cladding and induction cladding, iron-based coating is prepared on the surface of the cylinder liner, combining high content of chromium, nickel, molybdenum and other elements and rare earth oxides, the problem of insufficient corrosion resistance and wear resistance of the cylinder liner is solved. , more efficient coating preparation is achieved, reducing resource waste and production costs.

CN119194443APending Publication Date: 2024-12-27ZYNP CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411385130.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing cylinder liners have insufficient corrosion resistance and wear resistance in new energy methanol engines. Traditional overall casting leads to waste of resources. There are problems with the combination strength and pore defects in manual coating preparation, making it difficult to achieve ideal wear resistance and corrosion resistance. performance.

Method used

The iron-based coating is prepared on the surface of the cylinder liner by combining laser cladding and induction cladding. Carbides are formed through high content of chromium, nickel, molybdenum and other elements, combined with rare earth oxides, and the toughness and corrosion resistance of the coating are improved. And reduce internal stress and cracks through tempering.

Benefits of technology

It significantly improves the wear resistance and corrosion resistance of the cylinder liner, reduces pores and crack defects, improves the uniformity and crack resistance of the coating, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a preparation method of an iron-based coating, which comprises the following steps: S1) respectively arranging a laser head and an induction coil on two sides of a sample to be processed, spraying iron-based alloy powder from the laser head, and starting laser cladding from one side of the sample to be processed by the laser head; s2) after the laser head advances 4-6 cm on the surface of the to-be-processed sample, starting the induction coil until the end; and S3) tempering the sample obtained in the step S2). The invention further provides a preparation device of the iron-based coating. According to the preparation method of the iron-based coating, preparation of the iron-based coating is achieved through combination of laser cladding and induction cladding, the problems that the coating is prone to cracking and poor in compactness due to independent laser cladding are solved, generation of defects such as pores and cracks of the coating can be greatly reduced, and the wear resistance and corrosion resistance of the iron-based coating are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cylinder liner preparation, and in particular to a preparation method and a preparation device for an iron-based coating. Background Art

[0002] New energy methanol engines are prone to produce acid mist such as formic acid during use, which makes the cylinder liner not resistant to corrosion. At the same time, the existing general cylinder liner materials have poor wear resistance. In order to adapt to the wear resistance and corrosion resistance of new energy, the cylinder liner material is often changed, and the performance requirements are met by adding wear-resistant and corrosion-resistant alloys. However, since the cylinder liner is an integral casting, this will waste a lot of resources and precious metals. At the same time, in order to increase wear resistance, a quenching process is often added to the surface. Although the hardness and wear resistance are improved, the corrosion resistance cannot be fundamentally solved.

[0003] When the cylinder liner is working, only a very thin layer on the surface is involved in wear and contact with the combustion gas. Therefore, the wear and contact areas need to have sufficient hardness, strength, and corrosion resistance. Therefore, adding a layer of wear-resistant and corrosion-resistant coating on the surface of the cylinder liner to meet performance requirements also saves a lot of alloy additions and reduces production costs.

[0004] Due to the structural characteristics of the cylinder liner, the method of coating the cylinder liner surface is generally manual application and drying without composite treatment. Its wear resistance and corrosion resistance are affected by factors such as the voids and bonding strength of the coating, and often fail to achieve the desired effect. At the same time, manual operation is time-consuming and labor-intensive, and there are also problems with bonding strength and pore defects.

[0005] Therefore, in order to achieve the wear resistance and corrosion resistance of the cylinder liner, it is of great significance to provide a preparation method of the cylinder liner coating which is easy to operate and has stable performance. Summary of the invention

[0006] The technical problem solved by the present invention is to provide a method for preparing an iron-based coating. The iron-based coating prepared in the present application has good wear resistance and corrosion resistance.

[0007] In view of this, the present application provides a method for preparing an iron-based coating, comprising the following steps:

[0008] S1) a laser head and an induction coil are respectively arranged on both sides of the sample to be processed, and iron-based alloy powder is ejected from the laser head, and the laser head starts laser cladding from one side of the sample to be processed;

[0009] S2) after the laser head moves 4 to 6 cm on the surface of the sample to be processed, the induction coil is turned on until the end;

[0010] S3) tempering the sample obtained in step S2);

[0011] The iron-based alloy powder comprises: 20-35wt% Cr, 0.5-2wt% C, 1-5wt% Si, 2-5wt% Ni, 0.5-2wt% Mo, 2-4wt% La2O3, 0.5-1.5wt% CeO2, and balance Fe.

[0012] Preferably, the composition of the sample to be processed includes: C 2.8~3.5wt%, Si 1.8~2.8wt%, Mn 0.6~1.2wt%, P≤0.2wt%, S≤0.1wt%, Cu≤0.3wt%, Fe balance; the sample to be processed is a cylinder liner; the sample to be processed is placed on an automatically rotating shaft roller.

[0013] Preferably, the distance between the laser head and the induction coil is 5-10 cm.

[0014] Preferably, the angle between the laser head and the sample to be processed is 20°~40°.

[0015] Preferably, the laser power of the laser head is 4.5~5.5KW, the scanning speed is 200~300mm / s, the beam shape is 1x15mm, the number of scans is 1 time, the powder feeding speed is 25~35mg / s, and the coating thickness is 0.5~1.0mm.

[0016] Preferably, the inductor oscillation frequency of the induction coil is 150-250 kHz, the oscillation power is 90-100 kW, the gap between the induction coil and the sample to be processed is 3.5-5.5 mm, and the argon gas flow rate is 2.5-3.5 L / mm.

[0017] Preferably, the rotation speed of the shaft roller is 50-100 rpm, and the laser is turned on 20-30 seconds after the shaft roller is started.

[0018] Preferably, the tempering temperature is 450-500° C. and the time is 1-3 hours.

[0019] Preferably, the tempering further includes honing, and the honing depth is 0.1-0.3 mm.

[0020] The present application also provides a device for preparing the iron-based coating, comprising a laser spraying device, an induction heating device, a shaft roller and a motor, wherein the laser spraying device comprises a laser and a laser head connected in sequence, the induction heating device comprises an inductor and an induction head connected to the inductor on one side, an induction coil is arranged on the other side of the induction head, the motor is connected to the shaft roller, the sample to be processed is placed on the shaft roller, and the laser head and the induction head are arranged on both sides of the sample to be processed.

[0021] The present application provides a method for preparing an iron-based coating, wherein a laser head and an induction coil are respectively arranged on both sides of a sample to be processed, an iron-based alloy powder is sprayed out from the laser head, and the laser head starts laser cladding from one side of the sample to be processed, and the induction coil is turned on after the laser head moves 4 to 6 cm on the surface of the sample to be processed, and the laser is in front and the induction is in the back until the spraying and cladding are completed, and finally tempering is performed to obtain a sample with an iron-based coating on the surface; in order to avoid the problems of cracking and poor density caused by laser cladding alone, the present application performs induction cladding at the same time as laser coating, which greatly reduces the possibility of pores and crack defects in the iron-based coating, and at the same time, the uniformity of the coating is also improved; in order to eliminate the internal stress and brittleness of laser cladding and composite induction cladding, and reduce the occurrence of tearing during honing, finally tempering is performed to further improve wear resistance and corrosion resistance.

[0022] Furthermore, the iron-based alloy powder contains a high content of chromium. Since chromium forms chromium-containing carbides at high temperatures, the carbon content is high and located at or near the eutectic point. The narrow solidification range of the eutectic point alloy, small grains and good toughness are used to improve the anti-cracking ability of the cladding coating. At the same time, most areas of the cladding layer are in a non-equilibrium, sub-crystalline state, with fine structure and strong and tough two-phase microstructure characteristics. Adding nickel can improve the toughness of the coating to reduce the cracking tendency of the coating, but the increase of the toughness phase will lead to a decrease in the hardness of the coating, so the nickel The amount of molybdenum added should be strictly controlled; in order to increase the formation of carbides and make the carbides have diverse forms, a certain amount of molybdenum is added. At this time, there are two forms of carbides, namely, the uniform precipitation of γ→M23C6, γ→M2C and the in-situ transformation of M7C3→M23C6, M7C3→M6C. The coating has a significant secondary hardening phenomenon; the addition of rare earth oxides such as lanthanum trioxide and cerium dioxide can effectively desulfurize and deoxidize, promote the nucleation rate, thereby obtaining a coating with refined structure and reduced porosity, which effectively improves the wear resistance and corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the production process of the cylinder liner of the present invention;

[0024] Figure 2 A schematic diagram of a device for preparing an iron-based coating according to the present invention;

[0025] Figure 3 This is a metallographic structure photograph of the iron-based coating prepared in Example 1 of the present invention;

[0026] Figure 4 This is a metallographic photograph of the iron-based coating prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0027] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0028] In view of the performance requirements of wear resistance and corrosion resistance of cylinder liners in the prior art, the present application provides a method for preparing an iron-based coating, which composites an iron-based coating on the surface of a sample to be processed by laser cladding and induction cladding, thereby preventing the problem of cracking and poor density of the coating caused by laser cladding alone. Laser cladding composite induction cladding can greatly reduce the generation of defects such as pores and cracks in the coating, and improve the wear resistance and corrosion resistance of the iron-based coating; at the same time, the uniformity of the coating is greatly improved, and the cladding speed is increased. Specifically, an embodiment of the present invention discloses a method for preparing an iron-based coating, comprising the following steps:

[0029] S1) a laser head and an induction coil are respectively arranged on both sides of the sample to be processed, and iron-based alloy powder is ejected from the laser head, and the laser head starts laser cladding from one side of the sample to be processed;

[0030] S2) after the laser head moves 4 to 6 cm on the surface of the sample to be processed, the induction coil is turned on until the end;

[0031] S3) tempering the sample obtained in step S2);

[0032] The iron-based alloy powder comprises: 20-35wt% Cr, 0.5-2wt% C, 1-5wt% Si, 2-5wt% Ni, 0.5-2wt% Mo, 2-4wt% La2O3, 0.5-1.5wt% CeO2, and balance Fe.

[0033] During the preparation of the iron-based coating, the present application respectively arranges a laser head and an induction coil on both sides of the sample to be processed, and preferably places the sample to be processed flat on an automatically rotating shaft roller, and drives the sample to be processed by the rotation of the shaft roller; in the present application, the spacing between the laser head and the induction coil is 5 to 10 cm. If the laser cladding starts from the left end of the sample to be processed, the laser head is arranged at the left end of the sample to be processed, and the spacing between the laser head and the induction coil is 5 to 10 cm. According to the characteristics of laser cladding and induction cladding of the present application, the size of the sample to be processed is at least greater than 10 cm, so that the laser cladding needs to advance 4 to 6 cm on the surface of the sample to be processed before induction cladding is performed.

[0034] The iron-based alloy powder is put into the material box of the laser and sprayed out from the laser head. The angle between the laser head and the sample to be processed is 20°~40°. When the electrode drives the shaft roller to rotate, the sample to be processed rotates. At this time, the iron-based alloy powder in the laser is sprayed out from the laser head and coated on the surface of the sample to be processed for laser cladding. At the same time, the laser head moves from one end of the sample to be processed to the other end. After the laser head moves 4~6cm, the induction coil starts to work. From then on, the laser head is in front and the induction coil is behind until the spraying of the sample to be processed is completed.

[0035] The above-mentioned laser cladding realizes the preparation of the coating. The induction cladding is used for heating on the one hand and remelting the laser sprayed coating on the other hand to change the structure to obtain carbides with uniform structure, reduce the pores and crack tendency of the coating, so that the iron-based coating can achieve wear resistance and corrosion resistance.

[0036] In a specific embodiment, the laser head starts coating from the left end of the sample to be processed, and then the laser head performs laser cladding from the left end to the right end of the sample to be processed. When the laser head moves 5 cm on the surface of the sample to be processed, that is, the laser coating is performed for 5 cm, the induction coil starts to work. From then on, the laser head is on the left and the induction coil is on the right to perform a combination of laser cladding and induction cladding until the surface processing of the sample to be processed is completed. When the iron-based coating of the sample to be processed reaches the set length (which can be set according to the length of the cylinder sleeve), the laser will stop automatically. At this time, the shaft roller motor and the induction device are still working (the laser head is on the left and the induction coil is on the right. When the laser completes the set length, the induction has not yet been completed). When the induction head reaches the set length, the inductor stops heating and returns to its original position. At this time, the cylinder sleeve is taken out and the next operation can be performed.

[0037] In the above preparation process, the iron-based alloy powder includes: Cr 20~35wt%, C 0.5~2wt%, Si 1~5wt%, Ni 2~5wt%, Mo 0.5~2wt%, La2O3 2~4wt%, CeO2 0.5~1.5wt%, and Fe balance.

[0038] Among them, the Cr content is relatively high. Cr can form Cr-containing carbides at high temperatures. The carbon content is also relatively high and is located at or near the eutectic point. The characteristics of the eutectic point alloy with a narrow solidification range, small grains and good toughness are utilized to improve the ability of the cladding coating to resist cracking; the Cr content is 20~35wt%, specifically, the Cr content is 24~33wt%, and more specifically, the Cr content is 28~30wt%; for example, the Cr content in this application is 21wt%, 22wt%, 23wt%, 25wt%, 26wt%, 27wt%, 29wt%, 31wt%, 32wt%, and 34wt%.

[0039] Ni can improve the toughness of the coating to reduce the tendency of the coating to crack, but the increase in the toughness phase will lead to a decrease in the hardness of the coating, so the Ni content needs to be strictly controlled; the Ni content is 2~5wt%, specifically, the Ni content is 2.5~4.5wt%, more specifically, the Ni content is 3.5~4wt%; for example, the Ni content in this application is 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.6wt%, 3.7wt%, 3.9wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.6wt%, and 4.8wt%.

[0040] In order to increase the formation of carbides and make the carbides have diverse forms, a certain amount of molybdenum is added. At this time, there are two forms of carbides, namely, γ→M23C6, γ→M2C uniform precipitation and M7C3→M23C6, M7C3→M6C in-situ transformation. The content of Mo is 0.5~2wt%, specifically, the content of Mo is 0.8~1.8wt%, more specifically, the content of Mo is 1.0~1.6wt%; for example, the content of Mo in this application is 0.6wt%, 0.7wt%, 0.9wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.7wt%, 1.9wt%.

[0041] The C content is 0.5~2wt%, specifically, the C content is 0.8~1.9wt%, more specifically, the C content is 1.5~1.8wt%; for example, the C content in this application is 0.6wt%, 0.7wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.6wt%, and 1.7wt%.

[0042] La2O3 and CeO2 have the ability to effectively desulfurize and deoxidize, promote the nucleation rate, thereby refining the structure and reducing the porosity. The content of La2O3 is 2~4wt%, specifically, the content of La2O3 is 2.5~3.8wt%, more specifically, the content of La2O3 is 3~3.4wt%; for example, the content of La2O3 in this application is 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.9wt%. The content of CeO2 is 0.5~1.5wt%, specifically, the content of CeO2 is 0.8~1.4wt%; for example, the content of CeO2 in this application is 0.6wt%, 0.7wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, and 1.3wt%.

[0043] The laser power of the laser head is 4.5~5.5KW, the scanning speed is 200~300mm / s, the beam shape is 1x15mm, the number of scans is 1, the powder feeding speed is 25~35mg / s, and the coating thickness is 0.5~1.0mm; specifically, the laser power of the laser head is 4.7~5.3KW, the scanning speed is 230~280mm / s, and the powder feeding speed is 27~32mg / s; more specifically, the laser power of the laser head is 4.8~5.0KW, the scanning speed is 250~270mm / s, and the powder feeding speed is 28~30mg / s.

[0044] The inductor oscillation frequency of the induction coil is 150~250kHz, the oscillation power is 90~100KW, the gap between the induction coil and the sample to be processed is 3.5~5.5mm, and the argon gas flow rate is 2.5~3.5L / mm; specifically, the inductor oscillation frequency of the induction coil is 180~235kHz, the oscillation power is 92~98KW, the gap between the induction coil and the sample to be processed is 3.8~5.0mm, and the argon gas flow rate is 2.8~3.3L / mm; more specifically, the inductor oscillation frequency of the induction coil is 200~230kHz, the oscillation power is 93~96KW, the gap between the induction coil and the sample to be processed is 4.0~4.5mm, and the argon gas flow rate is 2.9~3.0L / mm.

[0045] The rotation speed of the shaft roller is 50-100 rpm, and the laser is turned on 20-30 seconds after it is started.

[0046] In the present application, the composition of the sample to be processed is preferably: C 2.8~3.5wt%, Si 1.8~2.8wt%, Mn0.6~1.2wt%, P≤0.2wt%, S≤0.1wt%, Cu≤0.3wt%, Fe balance; specifically, C 2.98~3.35wt%, Si1.90~2.64wt%, Mn 0.72~1.08wt%, P≤0.15wt%, S≤0.07wt%, Cu≤0.25wt%, Fe balance; more specifically, C 3.0~3.2wt%, Si 2.0~2.34wt%, Mn 0.82~1.0wt%, P≤0.06wt%, S≤0.05wt%, Cu≤0.2wt%, Fe balance.

[0047] After the above cladding is completed, tempering is performed to eliminate the internal stress and brittleness in the coating after the laser cladding and induction cladding are combined, and to reduce the tearing during the honing process. The tempering temperature is 450-500°C and the time is 1-3 hours; specifically, the tempering temperature is 460-490°C and the time is 2-3 hours; more specifically, the tempering temperature is 470-480°C.

[0048] The tempered sample is finally honed to meet the inner diameter requirement of the sample. The honed thickness is 0.1-0.3 mm, and specifically, the honed thickness is 0.15-0.25 mm.

[0049] The preparation method of the iron-based coating provided in the present application is mainly aimed at the preparation of the iron-based coating on the surface of the cylinder liner, that is, the sample to be processed is the cylinder liner, and the coating area on the surface of the cylinder liner that needs to be prepared is prepared by the above method; Figure 1 As shown, specifically: firstly, a cylinder liner blank is prepared according to the existing method, and then the cylinder liner blank is subjected to rough machining and fine machining in sequence to obtain a cylinder liner semi-finished product; the cylinder liner semi-finished product is cleaned and placed on a shaft roller, and laser cladding is performed using a laser head; during the laser cladding process, the laser head automatically starts induction cladding after traveling 4 to 6 cm on the surface of the cylinder liner semi-finished product to obtain a composite cladding cylinder liner, and finally a tempering treatment is performed to obtain the cylinder liner; in order to meet the size requirements of the cylinder liner, honing of the cylinder liner is also included.

[0050] Furthermore, the present application also provides a device for preparing an iron-based coating, including a laser spraying device, an induction heating device, a shaft roller and a motor, the laser spraying device including a laser and a laser head connected in sequence, the induction heating device including an inductor and an induction head connected to the inductor on one side, an induction coil is provided on the other side of the induction head, the motor is connected to the shaft roller, the sample to be processed is placed on the shaft roller, and the laser head and the induction head are arranged on both sides of the sample to be processed.

[0051] The electrodes, lasers and sensors are all connected to a central controller via wires, and the central controller realizes the automated preparation of the iron-based coating according to the set parameters.

[0052] The sample to be processed is taken as a cylinder sleeve, and the schematic diagram of the preparation device of the iron-based coating is as follows: Figure 2 As shown, 1 is a cylinder liner, 2 is a motor, 3 is a shaft roller, 4 is an adjustment laser, 5 is a laser head, 6 is a sensor, 7 is an induction head, 8 is an induction coil, 9 is a prepared iron-based coating, and 10 is a powder delivery pipe.

[0053] In order to further understand the present invention, the preparation method of the iron-based coating provided by the present invention is described in detail below in conjunction with examples, and the protection scope of the present invention is not limited by the following examples.

[0054] Example 1

[0055] A gray cast iron cylinder with a composition of C: 3.20%, S: 0.05%, Si: 2.34%, P: 0.08%, Mn: 0.82%, Cu: 0.20%, and Fe as the remainder is prepared according to the above proportions, and then subjected to conventional centrifugal casting to obtain a blank, and then the blank is subjected to rough machining and fine machining in sequence to obtain a semi-finished product, with a certain coating margin left in the inner hole, and then it is cleaned to remove oil and impurities, and dried to obtain a primary cylinder liner;

[0056] according to Figure 2 Schematic diagram, the cylinder liner primary product 1 is placed in a fixed position on the shaft roller 3, and the position can be adjusted according to the length of the cylinder liner;

[0057] Adjust the laser 4 so that the laser head 5 is tilted at an angle of 30°, and keep a certain distance between the laser head 5 and the cylinder liner primary product 1, and align the laser head 5 with the left end of the cylinder liner primary product 1; set the laser power to 5.0KW, scanning speed: 250mm / s, beam shape: 1x15mm, scanning times: 1 time, powder feeding speed: 30mg / s;

[0058] An iron-based alloy powder containing Cr: 28%, C: 1.5%, Si: 3.5%, Ni: 3.5%, Mo: 1%, La2O3: 3%, CeO2: 1.0%, and the balance being iron is loaded into the hopper of the laser 4, and the iron-based alloy powder is ejected through the alloy powder pipeline inside the laser head 5;

[0059] At this time, the sensor 6 is set to have an oscillation frequency of 200KHz, an oscillation power of 90KW, a gap of 4.5mm between the induction coil 8 and the cylinder sleeve 1, an argon gas flow rate of 3L / mm, and a distance of 10cm between the induction head 7 and the laser head 5;

[0060] Set the speed of the motor 2 of the shaft roller 3 to 80RPM and set the length of the cylinder sleeve at the same time;

[0061] After the setting is completed, start the click switch, and the iron-based alloy powder is sprayed from the laser head 5 to form a coating from the left end of the cylinder liner primary product 1. When the laser head 5 moves from the left end of the cylinder liner 1 for 5 minutes, the induction head 7 starts to work. After that, the laser head 5 is in front and the induction head 7 is in the back until the entire cylinder liner primary product 1 is sprayed and sensed. The entire laser and induction combination is automatically completed to obtain a cylinder liner with composite laser and induction;

[0062] Put the cylinder liner into the tempering furnace, set the tempering furnace temperature to 480℃, and keep it warm for 2h;

[0063] Finally, the cylinder liner is taken out of the tempering furnace and placed on a honing machine to hone the inner hole. The honing depth is about 0.15mm to obtain the finished cylinder liner.

[0064] Samples were taken from the finished cylinder liner for testing, and the hardness was 56HRC, the thickness was 0.5mm, the wear resistance weight loss was 0.00042g, and the formic acid resistance test was 0.012μm.

[0065] Example 2

[0066] A gas sleeve cylinder made of gray cast iron with a composition of C: 3.20%, S: 0.05%, Si: 2.34%, P: 0.08%, Mn: 0.82%, Cu: 0.20%, and Fe as the remainder is prepared according to the above proportions, and then subjected to conventional centrifugal casting to obtain a blank, and then the blank is subjected to rough machining and fine machining to obtain a semi-finished product, with a certain coating margin left in the inner hole, and then it is cleaned to remove oil and impurities, and dried to obtain a primary cylinder sleeve product;

[0067] according to Figure 2 Schematic diagram, the cylinder liner primary product 1 is placed in a fixed position on the shaft roller 3, and the position can be adjusted according to the length of the cylinder liner;

[0068] Adjust the laser 4 so that the laser head 5 is tilted at an angle of 25° and keep a certain distance between the laser head 5 and the cylinder liner primary product 1, and at the same time align the laser head 5 with the left end of the cylinder liner primary product 1; set the laser power to 4.7KW, scanning speed: 280mm / s, beam shape: 1x15mm, scanning times: 1 time, powder feeding speed: 35mg / s;

[0069] An iron-based alloy powder containing Cr: 33%, C: 1.9%, Si: 2.5%, Ni: 4.5%, Mo: 1.6%, La2O3: 3.8%, CeO2: 0.8%, and the balance being iron is loaded into the hopper of the laser 4, and the iron-based alloy powder is ejected through the alloy powder pipeline inside the laser head 5;

[0070] At this time, the sensor 6 is set to an oscillation frequency of 235KHz, an oscillation power of 90KW, a gap of 4.0mm between the induction coil 8 and the cylinder sleeve 1, an argon gas flow rate of 2.8L / mm, and a distance of 10cm between the induction head 7 and the laser head 5;

[0071] Set the speed of the motor 2 of the shaft roller 3 to 60RPM and set the length of the cylinder sleeve at the same time;

[0072] After the setting is completed, start the click switch, and the iron-based alloy powder is sprayed from the laser head 5 to form a coating from the left end of the cylinder liner primary product 1. When the laser head 5 moves from the left end of the cylinder liner 1 for 5 minutes, the induction head 7 starts to work. After that, the laser head 5 is in front and the induction head 7 is in the back until the entire cylinder liner primary product 1 is sprayed and sensed. The entire laser and induction combination will be automatically completed to obtain a cylinder liner with composite laser and induction;

[0073] Put the cylinder liner into the tempering furnace, set the tempering furnace temperature to 480℃, and keep it warm for 2h;

[0074] Finally, the cylinder liner is taken out of the tempering furnace and placed on a honing machine to hone the inner hole. The honing depth is about 0.15mm to obtain the finished cylinder liner.

[0075] Sampling was taken from the finished cylinder liner for testing, with the hardness being 58HRC, thickness being 0.48mm, wear resistance weight loss being 0.0003g, and formic acid resistance being 0.013μm.

[0076] Example 3

[0077] A gas sleeve cylinder made of gray cast iron with a composition of C: 2.98%, S: 0.04%, Si: 2.64%, P: 0.15%, Mn: 1.08%, Cu: 0.25%, and Fe as the remainder is prepared according to the above proportions, and then subjected to conventional centrifugal casting to obtain a blank, and then the blank is subjected to rough machining and fine machining in sequence to obtain a semi-finished product, with a certain coating margin left in the inner hole, and then it is cleaned to remove oil and impurities, and dried to obtain a primary cylinder sleeve product;

[0078] according to Figure 2 Schematic diagram, the cylinder liner primary product 1 is placed in a fixed position on the shaft roller 3, and the position can be adjusted according to the length of the cylinder liner;

[0079] Adjust the laser 4 so that the laser head 5 is tilted at an angle of 25°, and keep a certain distance between the laser head 5 and the cylinder liner primary product 1, and align the laser head 5 with the left end of the cylinder liner primary product 1; set the laser power to 4.8KW, scanning speed: 230mm / s, beam shape: 1x15mm, scanning times: 1 time, powder feeding speed: 32mg / s;

[0080] An iron-based alloy powder containing Cr: 24%, C: 0.8%, Si: 4.5%, Ni: 4.5%, Mo: 0.8%, La2O3: 2.5%, CeO2: 1.4%, and the balance being iron is loaded into the hopper of the laser 4, and the iron-based alloy powder is ejected through the alloy powder pipeline inside the laser head 5;

[0081] At this time, the sensor 6 is set to have an oscillation frequency of 180KHz, an oscillation power of 90KW, a gap between the induction coil 8 and the cylinder sleeve 1 of 3.8mm, an argon gas flow rate of 2.9L / mm, and a distance between the induction head 7 and the laser head 5 of 6cm;

[0082] Set the speed of the motor 2 of the shaft roller 3 to 90RPM and set the length of the cylinder sleeve at the same time;

[0083] After the setting is completed, start the click switch, and the iron-based alloy powder is sprayed from the laser head 5 to form a coating from the left end of the cylinder liner primary product 1. When the laser head 5 moves from the left end of the cylinder liner 1 for 5 minutes, the induction head 7 starts to work. After that, the laser head 5 is in front and the induction head 7 is in the back until the entire cylinder liner primary product 1 is sprayed and sensed. The entire laser and induction combination is automatically completed to obtain a cylinder liner with composite laser and induction;

[0084] Put the cylinder liner into the tempering furnace, set the tempering furnace temperature to 475℃, and keep it warm for 2h;

[0085] Finally, the cylinder liner is taken out of the tempering furnace and placed on a honing machine to hone the inner hole. The honing depth is about 0.15mm to obtain the finished cylinder liner.

[0086] Samples were taken from the finished cylinder liner for testing, and the hardness was 59HRC, the thickness was 0.51mm, the wear resistance weight loss was 0.0003g, and the formic acid resistance test was 0.016μm.

[0087] Example 4

[0088] A gas sleeve cylinder made of gray cast iron with a composition of C: 3.35%, S: 0.07%, Si: 1.90%, P: 0.06%, Mn: 0.72%, Cu: 0.13%, and Fe as the remainder is prepared according to the above proportions, and then subjected to conventional centrifugal casting to obtain a blank, and then the blank is subjected to rough machining and fine machining to obtain a semi-finished product, with a certain coating margin left in the inner hole, and then it is cleaned to remove oil and impurities, and dried to obtain a primary cylinder sleeve;

[0089] according to Figure 2 Schematic diagram, the cylinder liner primary product 1 is placed in a fixed position on the shaft roller 3, and the position can be adjusted according to the length of the cylinder liner;

[0090] Adjust the laser 4 so that the laser head 5 is tilted at an angle of 25° and keep a certain distance between the laser head 5 and the cylinder liner primary product 1, and align the laser head 5 with the left end position; adjust and set the laser power to 5.4KW, scanning speed: 300mm / s, beam shape: 1x15mm, scanning times: 1 time, powder feeding speed: 27mg / s;

[0091] The iron-based alloy powder containing Cr: 30%, C: 1.80%, Si: 1.5%, Ni: 2.5%, Mo: 1.8%, La2O3: 3.4%, CeO2: 0.8%, and the balance being iron is loaded into the hopper of the laser 4, and the iron-based alloy powder is ejected through the alloy powder pipeline inside the laser head 5;

[0092] At this time, the sensor 6 is set to have an oscillation frequency of 230KHz, an oscillation power of 90KW, a gap of 4.0mm between the induction coil 8 and the cylinder sleeve 1, an argon gas flow rate of 3.3L / mm, and a distance of 10cm between the induction head 7 and the laser head 5;

[0093] Set the speed of the motor 2 of the shaft roller 3 to 75RPM and set the length of the cylinder sleeve;

[0094] After the setting is completed, start the click switch, and the iron-based alloy powder is sprayed from the laser head 5 to form a coating from the left end of the cylinder liner primary product 1. When the laser head 5 moves from the left end of the cylinder liner 1 for 5 minutes, the induction head 7 starts to work. After that, the laser head 5 is in front and the induction head 7 is in the back until the entire cylinder liner primary product 1 is sprayed and sensed. The entire laser and induction combination will be automatically completed to obtain a cylinder liner with composite laser and induction;

[0095] Put the cylinder liner into the tempering furnace, set the tempering furnace temperature to 480℃, and keep it warm for 2h;

[0096] Finally, the cylinder liner is taken out of the tempering furnace and placed on a honing machine to hone the inner hole. The honing depth is about 0.15mm to obtain the finished cylinder liner.

[0097] Samples were taken from the finished cylinder liner for testing, with a hardness of 60HRC, a thickness of 0.65mm, a wear resistance weight loss of 0.0002g, and a formic acid resistance test of 0.014μm.

[0098] Comparative Example 1

[0099] According to the process of Example 1, but without induction heating, the other processes are the same as those of Example 1, as follows:

[0100] A gray cast iron cylinder with a composition of C: 3.20%, S: 0.05%, Si: 2.34%, P: 0.08%, Mn: 0.82%, Cu: 0.20%, and Fe as the remainder is prepared according to the above proportions, and then subjected to conventional centrifugal casting to obtain a blank, and then the blank is subjected to rough machining and fine machining in sequence to obtain a semi-finished product, with a certain coating margin left in the inner hole, and then it is cleaned to remove oil and impurities, and dried to obtain a primary cylinder liner;

[0101] according to Figure 2 Schematic diagram, the cylinder liner primary product 1 is placed in a fixed position on the shaft roller 3, and the position can be adjusted according to the length of the cylinder liner;

[0102] Adjust the laser 4 so that the laser head 5 is tilted at an angle of 30° and keep a certain distance between the laser head 5 and the cylinder liner primary product 1. At the same time, align the laser head 5 with the left end of the cylinder liner primary product 1 and adjust the sensor head to the rightmost end of the cylinder liner. Adjust and set the laser power to 5.0KW, scanning speed: 250mm / s, beam shape: 1x15mm, scanning times: 1 time, powder feeding speed: 30mg / s.

[0103] The iron-based alloy powder containing Cr: 28%, C: 1.5%, Si: 3.5%, Ni: 3.5%, Mo: 1%, La2O3: 3%, CeO2: 1.0%, and the balance being iron is loaded into the hopper of the laser 4, and the iron-based alloy powder is ejected through the alloy powder pipeline inside the laser head 5;

[0104] Set the speed of the motor 2 of the shaft roller 3 to 80 RPM and set the length of the cylinder sleeve at the same time;

[0105] After the setting is completed, start the click switch, and the iron-based alloy powder is sprayed from the laser head 5 to form a coating from the left end of the cylinder liner primary product 1 until the entire cylinder liner primary product 1 is sprayed. The entire laser cladding will be automatically completed to obtain a laser cladding cylinder liner;

[0106] Put the cylinder liner into the tempering furnace, set the tempering furnace temperature to 480℃, and keep it warm for 2h;

[0107] Finally, the cylinder liner is taken out of the tempering furnace and placed on a honing machine to hone the inner hole. The honing depth is about 0.15mm to obtain the finished cylinder liner.

[0108] Samples were taken from the finished cylinder liner for testing and analysis. The results are shown in Table 1

[0109] Comparative Example 2

[0110] According to the process of Example 1, no tempering treatment is performed, and other processes are the same as Example 1, as follows:

[0111] A gray cast iron cylinder with a composition of C: 3.20%, S: 0.05%, Si: 2.34%, P: 0.08%, Mn: 0.82%, Cu: 0.20%, and Fe as the remainder is prepared according to the above proportions, and then subjected to conventional centrifugal casting to obtain a blank, and then the blank is subjected to rough machining and fine machining in sequence to obtain a semi-finished product, with a certain coating margin left in the inner hole, and then it is cleaned to remove oil and impurities, and dried to obtain a primary cylinder liner;

[0112] according to Figure 2 Schematic diagram, the cylinder liner primary product 1 is placed in a fixed position on the shaft roller 3, and the position can be adjusted according to the length of the cylinder liner;

[0113] Adjust the laser 4 so that the laser head 5 is tilted at an angle of 30°, and keep a certain distance between the laser head 5 and the cylinder liner primary product 1, and align the laser head 5 with the left end of the cylinder liner primary product 1; set the laser power to 5.0KW, scanning speed: 250mm / s, beam shape: 1x15mm, scanning times: 1 time, powder feeding speed: 30mg / s;

[0114] An iron-based alloy powder containing Cr: 28%, C: 1.5%, Si: 3.5%, Ni: 3.5%, Mo: 1%, La2O3: 3%, CeO2: 1.0%, and the balance being iron is loaded into the hopper of the laser 4, and the iron-based alloy powder is ejected through the alloy powder pipeline inside the laser head 5;

[0115] At this time, the sensor 6 is set to have an oscillation frequency of 200KHz, an oscillation power of 90KW, a gap of 4.5mm between the induction coil 8 and the cylinder sleeve 1, an argon gas flow rate of 3L / mm, and a distance of 10cm between the induction head 7 and the laser head 5;

[0116] Set the speed of the motor 2 of the shaft roller 3 to 80RPM and set the length of the cylinder sleeve at the same time;

[0117] After the setting is completed, start the click switch, and the iron-based alloy powder is sprayed from the laser head 5 to form a coating from the left end of the cylinder liner primary product 1. When the laser head 5 moves from the left end of the cylinder liner 1 for 5 minutes, the induction head 7 starts to work. After that, the laser head 5 is in front and the induction head 7 is in the back until the entire cylinder liner primary product 1 is sprayed and sensed. The entire laser and induction combination is automatically completed to obtain a cylinder liner with composite laser and induction;

[0118] Finally, the cylinder liner is placed on the honing machine to hone the inner hole. The honing depth is about 0.15mm to obtain the finished cylinder liner.

[0119] Samples were taken from the laser induction composite cladding cylinder liner for detection and analysis. The results are shown in Table 1

[0120] Comparative Example 3

[0121] According to the process of Example 1, but changing the ratio of the iron-based alloy powder, the other processes are the same as in Example 1, specifically as follows:

[0122] A gray cast iron cylinder with a composition of C: 3.20%, S: 0.05%, Si: 2.34%, P: 0.08%, Mn: 0.82%, Cu: 0.20%, and Fe as the remainder is prepared according to the above proportions, and then subjected to conventional centrifugal casting to obtain a blank, and then the blank is subjected to rough machining and fine machining in sequence to obtain a semi-finished product, with a certain coating margin left in the inner hole, and then it is cleaned to remove oil and impurities, and dried to obtain a primary cylinder liner;

[0123] according to Figure 2 Schematic diagram, the cylinder liner primary product 1 is placed in a fixed position on the shaft roller 3, and the position can be adjusted according to the length of the cylinder liner;

[0124] Adjust the laser 4 so that the laser head 5 is tilted at an angle of 30°, and keep a certain distance between the laser head 5 and the cylinder liner primary product 1, and align the laser head 5 with the left end of the cylinder liner primary product 1; set the laser power to 5.0KW, scanning speed: 250mm / s, beam shape: 1x15mm, scanning times: 1 time, powder feeding speed: 30mg / s;

[0125] The iron-based alloy powder containing Cr: 28%, C: 1.5%, Si: 3.5%, Ni: 3.5%, Mo: 1%, and the balance being iron is loaded into the hopper of the laser 4, and the iron-based alloy powder is ejected through the alloy powder pipeline inside the laser head 5;

[0126] At this time, the sensor 6 is set to have an oscillation frequency of 200KHz, an oscillation power of 90KW, a gap of 4.5mm between the induction coil 8 and the cylinder sleeve 1, an argon gas flow rate of 3L / mm, and a distance of 10cm between the induction head 7 and the laser head 5;

[0127] Set the speed of the motor 2 of the shaft roller 3 to 80RPM and set the length of the cylinder sleeve at the same time;

[0128] After the setting is completed, start the click switch, and the iron-based alloy powder is sprayed from the laser head 5 to form a coating from the left end of the cylinder liner primary product 1. When the laser head 5 moves from the left end of the cylinder liner 1 for 5 minutes, the induction head 7 starts to work. After that, the laser head 5 is in front and the induction head 7 is in the back until the entire cylinder liner primary product 1 is sprayed and sensed. The entire laser and induction combination is automatically completed to obtain a cylinder liner with composite laser and induction;

[0129] Put the cylinder liner into the tempering furnace, set the tempering furnace temperature to 480℃, and keep it warm for 2h;

[0130] Finally, the cylinder liner is taken out of the tempering furnace and placed on a honing machine to hone the inner hole. The honing depth is about 0.15mm to obtain the finished cylinder liner.

[0131] Samples were taken from the finished cylinder liner for testing and analysis, and the analysis results are shown in Table 1;

[0132] Table 1 Wear resistance and formic acid corrosion resistance of coatings prepared in Example 1 and Comparative Example 1

[0133]

[0134] It can be seen from Table 1 that the coating prepared by the present invention has the best formic acid corrosion resistance and wear resistance. In Comparative Example 1, since no induction heating was performed but only laser cladding was performed, there was a serious tendency to crack and there was partial porosity, so the wear resistance and formic acid corrosion resistance were worse than those in Example 1; in Comparative Example 2, no tempering treatment was performed and there was a large stress phenomenon; in Comparative Example 3, since no rare earth elements were added, its wear resistance and corrosion resistance were reduced.

[0135] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0136] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing an iron-based coating, comprising the following steps: S1) a laser head and an induction coil are respectively arranged on both sides of the sample to be processed, and iron-based alloy powder is ejected from the laser head, and the laser head starts laser cladding from one side of the sample to be processed; S2) After the laser head moves 4 to 6 cm on the surface of the sample to be processed, the induction coil is turned on until the end; S3) tempering the sample obtained in step S2); The iron-based alloy powder comprises: 20-35wt% Cr, 0.5-2wt% C, 1-5wt% Si, 2-5wt% Ni, 0.5-2wt% Mo, 2-4wt% La2O3, 0.5-1.5wt% CeO2, and balance Fe.

2. The preparation method according to claim 1, characterized in that: The composition of the sample to be processed includes: C 2.8~3.5wt%, Si 1.8~2.8wt%, Mn 0.6~1.2wt%, P≤0.2wt%, S≤0.1wt%, Cu≤0.3wt%, Fe balance; the sample to be processed is a cylinder sleeve; the sample to be processed is placed on an automatically rotating shaft roller.

3. The preparation method according to claim 2, characterized in that: The distance between the laser head and the induction coil is 5-10 cm.

4. The preparation method according to claim 2, characterized in that: The angle between the laser head and the sample to be processed is 20°~40°.

5. The preparation method according to claim 2, characterized in that: The laser power of the laser head is 4.5~5.5KW, the scanning speed is 200~300mm / s, the beam shape is 1x15mm, the number of scans is 1 time, the powder feeding speed is 25~35mg / s, and the coating thickness is 0.5~1.0mm.

6. The preparation method according to claim 2, characterized in that: The inductor oscillation frequency of the induction coil is 150-250 kHz, the oscillation power is 90-100 kW, the gap between the induction coil and the sample to be processed is 3.5-5.5 mm, and the argon gas flow rate is 2.5-3.5 L / mm.

7. The preparation method according to claim 2, characterized in that: The rotation speed of the shaft roller is 50-100 rpm, and the laser is turned on 20-30 seconds after the shaft roller is started.

8. The preparation method according to claim 2, characterized in that: The tempering temperature is 450-500° C. and the tempering time is 1-3 hours.

9. The preparation method according to claims 1 to 8, characterized in that: The tempering process also includes honing, and the depth of the honing is 0.1-0.3 mm.

10. The device for preparing an iron-based coating according to any one of claims 1 to 9 comprises a laser spraying device, an induction heating device, a shaft roller and a motor, wherein the laser spraying device comprises a laser and a laser head connected in sequence, the induction heating device comprises an inductor and an induction head connected to the inductor on one side, an induction coil is arranged on the other side of the induction head, the motor is connected to the shaft roller, the sample to be processed is placed on the shaft roller, and the laser head and the induction head are arranged on both sides of the sample to be processed.